Penyuluhan Anemia Dan Pemeriksaan Hemoglobin Pada Anak-Anak di Panti Asuhan Baiturrahmah, Kampar - Paulina, Ariza Julia; Fatmawati, Fatmawati; Fridayenti; Chandra Wijaya; Meimi Laila; Sisilia Indah Cahyani; Nada Idzdihari Adesti; Erva Roudhotul Jannah (LPPM UMRI, 2025)
Iron deficiency anemia is the most common nutritional deficiency in the world, 30% of the population. From the results of a household health survey in Indonesia, the incidence of iron deficiency anemia reached 48.1% in children under five and 47.3% in school-aged children. Iron deficiency can cause interference with the immune response, making it susceptible to infection, gastrointestinal disorders, impaired cognitive function, growth and development, and changes in behavior. Purpose: this service activity is to increase knowledge about iron deficiency anemia and determine the anemia status of orphaned children at the Baiturrahmah Rimbo Panjang Orphanage, Tambang District, Kampar Regency. Method: counseling was carried out about Iron deficiency anemia by doctor, to assess the level of knowledge given in the pre test and post test. In addition, blood hemoglobin levels arechecked to see anemia status. Result: Service activities in the form of counseling have succeeded in increasing the knowledge of children about anemia. Hemoglobin levels were checked and it was found that 73.5% of orphanage children had hemoglobin levels <11 g/dL, which means they were anemic. So further treatment is needed to reduce the incidence of anemia in orphanage children. Keywords: Iron deficiency anemia, hemoglobin, children, Kampar